Effectiveness of Bupivacaine Infiltration in Reducing Postoperative Pain in Patients Undergoing Percutaneous Nephrolithotomy: Bupivacaine Infiltration in Reducing Postoperative Pain in Percutaneous Nephrolithotomy - Raza, Ali; Khursheed, Sana; Ahmed, Waqas; Rajpar, Zakir Hussain; Soomro, Naveed; Kumar, Raj; Shah, Syed Zulfiquar Ali (Pakistan Journal of Health Sciences, 2024)
Percutaneous Nephrolithotomy is a standard way to treat large renal calculi because it is slightly invasive. One big problem with normal percutaneous nephrolithotomy, though, is that patients often have discomfort and pain at the nephrostomy place after the surgery. Objective: To evaluate the effectiveness of bupivacaine infiltration in reducing postoperative pain in patients undergoing percutaneous nephrolithotomy. Methods: The quasi-study lasted for six months at Liaquat National Hospital in Karachi. A total of 60 patients were recruited as Group A=30 patients (20ml/50mg of 0.25% bupivacaine) and Group B=30 patients (20ml of normal saline). All the patients had percutaneous nephrolithotomy and at the end of the operation; a 12 Fr nephrostomy tube was put in place. All patients were carefully watched, and their pain levels were measured using a visual analogue scale and computed as mean ± SD. Results: Group A had a mean age of 39.9 ± 12.9 years, and Group B had a mean age of 39.4 ± 11.2 years. There were 16 men (53.3%) and 14 women (46.7%) in Group A, and 20 men (66.7%) and 10 women (33.3%) in Group B. The average amount of pain after surgery was 2.07 ± 0.78 in Group A and 4.80 ± 0.92 in Group B. The p-value was found to be extremely significant, which means it was 0.0001. Conclusion: It was concluded that the postoperative pain score was significantly better in bupivacaine infiltration as compared to placebo in percutaneous nephrolithotomy.